2002
DOI: 10.1023/a:1020552501345
|View full text |Cite
|
Sign up to set email alerts
|

Mega-Dose Vitamins and Minerals in the Treatment of Non-Metastatic Breast Cancer: An Historical Cohort Study

Abstract: Breast cancer-specific survival and disease-free survival times were not improved for the vitamin/mineral treated group over those for the controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 13 publications
1
55
0
5
Order By: Relevance
“…A study that more directly addresses the issue of antioxidant use concurrently with cytotoxics is that of Lesperance, et al 24 In this trial, 90 patients with early stage breast cancer who were prescribed megadoses of combination vitamins, minerals, and other antioxidants concurrent with standard therapy were compared with 180 wellmatched controls. Breast cancer-specific survival (P ϭ .16) and disease-free survival (P ϭ 0.07) showed a trend toward worse survival in antioxidant-treated patients.…”
Section: Clinical Evidencementioning
confidence: 99%
“…A study that more directly addresses the issue of antioxidant use concurrently with cytotoxics is that of Lesperance, et al 24 In this trial, 90 patients with early stage breast cancer who were prescribed megadoses of combination vitamins, minerals, and other antioxidants concurrent with standard therapy were compared with 180 wellmatched controls. Breast cancer-specific survival (P ϭ .16) and disease-free survival (P ϭ 0.07) showed a trend toward worse survival in antioxidant-treated patients.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Long-term follow-up of these subjects showed that at a median follow-up of 6.5 years, all-cause mortality was significantly higher in the treated group (hazard ratio or HR 1.38; CI 1.03-1.85) [69]. A historical cohort control study of 90 women who had taken large doses of beta-carotene, vitamin C, niacin, selenium, coenzyme Q10, and zinc during their conventional therapy were compared with matched controls [70]. Overall survival was the same for the two groups, but a trend toward reduction in disease-free survival was noted (P ¼ .08).…”
Section: Antioxidantsmentioning
confidence: 99%
“…In a historical cohort study 90 patients with early stage breast cancer who had consumed high doses of combinations of vitamins, minerals and other antioxidants concurrent with standard chemotherapy, were compared with 180 matched controls, who received chemotherapy only [29]. Patients on supplements displayed worse breast cancer-specific survival and disease-free survival than the control group.…”
Section: Effect Of Diet Constituents On Chemotherapy: Clinical Evidenmentioning
confidence: 99%
“…Firstly we need more information on mechanisms of dietary constituents which may be pertinent to drug toxicity or efficacy. Nutritional pharmacology is a subject in its infancy, but the interest of health providers and biomedical researchers has recently grown considerably, as illustrated by the fact that there is now a journal specifically devoted to this topic ("Molecular Nutrition and dietary agents should be designed based on relevant preclinical data, and they should preferably employ doses which resemble dietary doses of these agents, to minimize the chance of unwanted effects mediated by "mega" doses, as exemplified above at the preclinical level for folate [29] and fatty acids [26]. Clinical studies should also include, if possible, measurement of pharmacokinetics and pharmacodynamics of the diet constituent, in order to enable rational interpretation of pharmacological and/or toxicological effects or their absence.…”
Section: Studying Potential Interactionsmentioning
confidence: 99%